Intergenerational income persistence: Evidence for the UK - Laura Van der Erve; Sonya Krutikova; Lindsey Macmillan; David Sturrock (Institute for Fiscal Studies (IFS), 2022)
Intergenerational mobility is a subject of a large literature in social science. It focuses on the association between parents' and children's economic wellbeing and receives significant attention because it speaks to the question of equality of opportunity (Torche, 2015), which many consider an important goal for society. Intergenerational mobility is a cross-cutting theme in the Deaton Review, which is touched upon in several of the core chapters, including on education, early childhood and race & ethnicity. Therefore, our aim is not to provide a comprehensive overview of this topic but rather to spotlight some of the newer directions in intergenerational mobility research within economics driven by changes in some key trends in the recent decades as well as growing availability of administrative data.
Keywords: 330; Intergenerationenmobilität; Schätzung; Großbritannien